Margaret Thatcher in Spitting Image - Yves Golder (Revue Française de Civilisation Britannique)
The main ambition of this article is to pay tribute to Jacques Leruez whose work came to constitute a reference for British civilisation researchers focusing on the twentieth century. It provides a study of the representation of Margaret Thatcher’s political image in the British television show called Spitting Image. This TV show was broadcast on ITV from 1984 to 1996. As that period included six years of her premiership, it is not surprising that Margaret Thatcher was one of the main characters in the show. Its aim was to offer a political caricature necessarily consisting in a distortion of reality. In the late twentieth century and, more precisely, in the 1980s, television developed as a means of communication throughout Western Europe thanks to the creation of new channels and the general deregulation of this market. As a consequence, it was increasingly used as a means of political propaganda or advertising whether by politicians themselves or by the media. One main ambition behind Spitting Image was to ridicule British politicians like Margaret Thatcher. Did the TV show succeed in building an efficient criticism thanks to its satirical dimension ? This contribution will first highlight the different ways in which Margaret Thatcher was caricatured by Spitting Image. More precisely, it will focus on four different forms of representations which seemed to prevail in the show. As for the conclusion, it will be devoted to the ways in which her caricature was generally perceived by her fellow citizens.